THE RELATIONSHIP BETWEEN REWARDING AND EXECUTIVE NURSE MOTIVATION AT PINNA TAMBUN BEKASI HOSPITAL IN 2023 - Rosidatul Husna; Kiki Deniati; Lisna Agustina (Rena Cipta Mandiri, 2024)
Nursing services provided by nurses greatly affect the quality of nursing care in order to achieve optimal health levels. A good quality of nursing care can be achieved if the nurse's work motivation is high. The existence of a reward will raise the spirit to work. So if the nurse already feels this enthusiasm from within herself, there will be motivation to increase productivity and show the best performance at work. By giving rewards with the aim of maintaining the motivation of these employees to always be in good condition, so that the quality of hospital services is increasing. The purpose of this study was to find out the relationship between giving rewards and the motivation of implementing nurses at Pinna Tambun Bekasi Hospital. The method in this study used a cross sectional research design with a total sampling technique and used a questionnaire via google form to 47 respondents at Pinna Tambun Bekasi Hospital. This study uses the chi-square statistical test to determine the relationship between the two variables. This study used the chi-square statistical test to determine the relationship between the two variables. Based on the results of the chi-square test analysis with a value of p = 0.001 (p <0.050), it is stated that H0 is rejected. So that it can be interpreted that there is a relationship between knowledge about Giving Rewards and the Motivation of Implementing Nurses at Pinna Tambun Bekasi Hospital in 2023.